Thermal loss analysis of hermetic compressors using numerical simulation. (5th February 2018) - Posch, S.; Hopfgartner, J.; Dür, L.; Eichinger, M.; Stangl, S.; Almbauer, R.
Highlights: A holistic numerical compressor simulation is proposed. An insight into the numerical simulation of the submodels is given. Special focus is laid on the modeling of the oil influence. A loss analysis in terms of entropy generation and exergy loss is carried out. Abstract: The present work deals with a comprehensive investigation of the thermal losses of a hermetic compressor for refrigeration application using numerical methods. In this case numerical models mean full 3d CFD simulation of the refrigerant path using fluid structure interaction to model the valve dynamics, 3d heat conduction in the solid parts of the compressor, 3d CFD simulation of the oil distribution inside the compressor shell to obtain heat transfer coefficients, 3d CFD of the oil flow in the oil pump and mechanical loss determination by solving the Reynolds equation numerically. Validation activities are carried out for both the submodels and the entire thermal model. Furthermore, the compressor losses are described in terms of entropy generation and exergy loss. The results are broken down into losses according to their location. The application of the methodology on a compressor with a cooled valve plate shows that the cooling capacity of the compressor at ASHRAE test conditions can be increased by 2.63% but the compressor COP is only increased by 1.57% due to the rise of the mechanical losses by the viscosity increase.